ChemInform Abstract: Carboxylic Acid Free Novel Isocyanide‐Based Reactions. Issue 20 (20th May 2014) - Soeta, Takahiro; Ukaji, Yutaka
Abstract Review: [design of novel Passerini‐ and Ugi‐type reaction systems where the carboxylic acid component has been replaced by compounds (Z—X) containing an electrophilic (Z) and a nucleophilic group (X); 40 refs.